Q Fever - An Unexpected Case Report - Fiúza, Pedro; Eusébio, Sofia; Soares, Raquel; Conchinha, André; Cunha, Sofia; Lopes, Adriana; Nascimento, Paula; Tosatto, Valentina (International Journal of Innovative Research in Medical Science, 2024)
We present a case of Q fever in a 77-year-old autonomous male with a complex medical history. The patient, immunocompromised due to azathioprine and prednisolone use for myasthenia gravis, also suffered from diabetes mellitus, heart failure, and severe asthma. Despite no history of animal contact or travel to endemic regions, the patient developed flu-like symptoms followed by high fever and prostration. Multiple courses of antibiotics were administered without clinical improvement, and cultures of blood, urine, and stool were negative. Serological testing for Coxiella burnetii confirmed the diagnosis, with positive IgG and IgM phase II antibodies. The patient received doxycycline therapy and experienced rapid clinical improvement, with sustained apyrexy and no recurrence of symptoms at a 2-week follow-up. This case highlights the diagnostic challenges of Q fever, particularly in immunocompromised individuals with multiple comorbidities. Despite the absence of typical exposure history, serological testing was crucial for confirming the diagnosis. The timely initiation of doxycycline therapy was essential for a favourable outcome.